2019
DOI: 10.1093/cid/ciz323
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Importance of Invasive Methicillin-sensitive Staphylococcus aureus Infections: Surveillance in 8 US Counties, 2016

Abstract: Background Public health and infection control prevention and surveillance efforts in the United States have primarily focused on methicillin-resistant Staphylococcus aureus (MRSA). We describe the public health importance of methicillin-susceptible S. aureus (MSSA) in selected communities. Methods We analyzed Emerging Infections Program surveillance data for invasive S. aureus (SA) infections (isolated from a normally steril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…The MSSA all belong to well-known clones, such as ST398 MSSA, which is human-associated unlike the MRSA ST398 [ 32 ] and carries the erm (T) gene, which are not typically found in livestock-associated strains [ 33 ]. Furthermore, future in-depth studies should also focus on the epidemiology of MSSA, as these strains account for the majority of invasive S. aureus infections in the United States resulting in considerable morbidity and mortality, [ 34 ] and may also pose a health risk for beachgoers.…”
Section: Discussionmentioning
confidence: 99%
“…The MSSA all belong to well-known clones, such as ST398 MSSA, which is human-associated unlike the MRSA ST398 [ 32 ] and carries the erm (T) gene, which are not typically found in livestock-associated strains [ 33 ]. Furthermore, future in-depth studies should also focus on the epidemiology of MSSA, as these strains account for the majority of invasive S. aureus infections in the United States resulting in considerable morbidity and mortality, [ 34 ] and may also pose a health risk for beachgoers.…”
Section: Discussionmentioning
confidence: 99%
“…Methicillin-resistant S. aureus was originally considered a hospital-associated infection, but infection in previously healthy individuals in the community emerged in the 1990s and, so, it now is referred to as community-associated MRSA (CA-MRSA) [6]. The incidence of invasive S. aureus infection has increased in recent years, with similar frequently reported infections irrespective of the methicillin-resistant status (except for the association of methicillin-susceptible S. aureus (MSSA) with septic arthritis), although smaller studies have reported more pneumonia, bacteremia or sepsis, and endocarditis among MRSA patients [7, 8].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic studies of S. aureus have historically focused on methicillin-resistant S. aureus (MRSA) due to challenges in treatment and poorer clinical outcomes ( Dasenbrook et al, 2010 ; Harkins et al, 2018 ; Kanjilal et al, 2018 ). Yet methicillin-susceptible S. aureus (MSSA) strains continue to cause significant morbidity and mortality ( Jackson et al, 2019 ). In particular, some S. aureus strains produce epidermolytic staphylococcal exfoliative toxins (ETs), extracellular proteins that cause separation of the epidermal layer of the skin.…”
Section: Introductionmentioning
confidence: 99%